Modelamiento en MatLab de prótesis transtibial - Guardiola León, Daniel (Tekhnê, 2015)
This paper details the mathematical modeling (block diagram) of a transtibial prosthesis. The 3D design is analyzed in MatLab (SimMechanics toolbox) in order to know the answer to the different forces with which the prosthesis interacts during operation. As a criterion is assumed that the prothesis is carried by a man of 70 kg and 1.70 m. The human gait is emulated in MatLab by model blocks. Additionally, Opensim simulation software is used to understand the behavior of human kinematics.